Respon Pertumbuhan dan Hasil Tanaman Padi Sawah akibat Aplikasi Blue Green Algae dan Pupuk N - Mieke Rochimi Setiawati; Pujawati Suryatmana (Soilrens, 2019)
The growth and yield of rice plants is very dependent on nitrogen (N) fertilizer. N fertilizer applied to wetland rice mostly unutilized due to the lost through the process of denitrification and leaching. The presence of blue-green algae (BGA), procaryotic algae N2-fixing in the paddy field is advantageous to help to uptake the N for plants by direct fixation of N2 from air and then converted into cell proteins. Excess N fixation results were released into the BGA growth environment. BGA biomass at the latter stage will be mineralized to ammonium. Mineralized ammonium from BGA cells as a source of N that can be used directly by paddy plants. This experiment used a randomized block design with factorial pattern; BGA inoculant dose treatment consisted of: 0; 5 kg; 10 kg ha-1 and urea dose 30; 60; 90; 120 kg N ha-1. The results of this experiment showed that the use of BGA can increase the rate of growth of rice plants and reduced urea requirements by 25%. The combination of 90 kg ha-1 N fertilizer with 10 kg ha-1 Blue-green algae inoculant can increase grain yield by 31.47% per hectare (2.71 tons ha-1).